2008
DOI: 10.1080/13561820701714755
|View full text |Cite
|
Sign up to set email alerts
|

Providing interprofessional learning through interdisciplinary collaboration: The role of “modelling”

Abstract: Faculty from four disciplines at a small Liberal Arts College in an American Midwestern city collaborated on an interdisciplinary pre-service project. Students in nursing, physical therapy, social work and special education voluntarily participated in one of two group methods of teaching. The purpose of this study was to examine whether students learn interprofessional teaming more effectively from (i) discussion of research, faculty modeling and role-playing, or from (ii) discussion of research and role-playi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…As educators we should expect and foster this interest from students and openly discuss our own workplace experiences with patients and their families. Modeling interprofessional practice amongst teachers within classroom activities and discussions can assist in the preparation of students for actual interprofessional placement activities (Selle et al 2008). In addition, conversations with our practicing health profession colleagues suggest that for many the benefits and importance of interprofessional practices is often only truly realised after graduation once an individual commences practice.…”
Section: Tipmentioning
confidence: 99%
“…As educators we should expect and foster this interest from students and openly discuss our own workplace experiences with patients and their families. Modeling interprofessional practice amongst teachers within classroom activities and discussions can assist in the preparation of students for actual interprofessional placement activities (Selle et al 2008). In addition, conversations with our practicing health profession colleagues suggest that for many the benefits and importance of interprofessional practices is often only truly realised after graduation once an individual commences practice.…”
Section: Tipmentioning
confidence: 99%
“…As professional requirements for programs continue to increase, the importance of interprofessional collaboration cannot be minimized. 94 Furthermore, these authors also recognized that some of the greatest challenges to IPE were in overcoming historical and institutional barriers that stymied collaboration among educational programs in the health professions. This includes misconceptions about the roles and responsibilities athletic trainers have in the interprofessional health care team.…”
Section: Discussionmentioning
confidence: 99%
“…Selle et al 94 found that a program modeling interprofessional behaviors was quite successful, and that when evaluated, it showed that students desired interprofessional collaboration within the academic setting in preparation for entry into their individual professions. As professional requirements for programs continue to increase, the importance of interprofessional collaboration cannot be minimized.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling is the presentation of the values or behaviours of an admired person as an inducement to students to acquire those values or behaviours (Moore, 2001) or, what Guillaume (2000) refers to as learning by example. Modeling also demonstrates appropriate interactions with students, (Orstein & Lasley, 2001;Selle, Salamon & Sauer, 2008) and as such was a powerful instructional strategy. It has been found to be effective for learners of all ages and is appropriate in every subject area (Guillaume, 2000).…”
Section: A Framework For Exposing Pre-service Students To Interprofesmentioning
confidence: 99%